Some factors associated to cosmetic dentistry: a new approach - Becerra-Santos, Gerardo; Becerra-Moreno, Natalia; Jiménez-Arango, Marcela; Medina-Piedrahita, Verónica María; Tamayo-López, Laura Cecilia; Gómez, Sandra Liliana (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: the purpose of this study was to determine the behavior of some factors influencing dental esthetics in male and female students of Universidad de Antioquia School of Dentistry (FOUA for its Spanish initials), aged 18 to 30 years. Methods: this was a descriptivetransversal study on 203 FOUA students. Direct measurements of the six maxillary anterior teeth were recorded with a digital Vernier caliper (Digimatic)® and the lower third of the face was photographed. The statistical analysis was conducted with SPSS 17. Descriptive measurements were obtained and a Student’s t test was performed after testing normal distribution, in order to establish mean differences between the ideal proportions of lateral incisors. Results and conclusions: in males, the Facial Midline (FML) coincided with the Upper Teeth Line in 61.4% of the cases and both teeth lines coincided with each other in 38.6%. In females, the FML coincided with the Upper Teeth Line in 62.25% and both teeth lines coincided with each other in 31.1%. None of the subjects had the Golden Proportion between central and lateral upper incisors. The most prevalent Individual Tooth Ratio (ITR) range was the one over 80%. The average length of females’ upper lip was 21.41 mm and the bottom lip 47.18 mm; in males, the upper lip measured 22.78 mm in average and the bottom lip 52.45 mm. In both sexes, the most frequent position of the upper lateral incisors’ gingival margin was the incisal one.